PBDMS : personal bibliographic data management system - Goh, Chee Hong. (2009)
Personal Bibliographic Data Management System (PBDMS) is an Open Source peer-to-peer (P2P) social library application that is developed by an ex-NTU student. It can be deployed to work as a standalone application or collaborate with other machines that have PBDMS installed on. The current version of PBDMS allows users to manage their electronic documents on their local computer, share them with their peers, search the network for documents and provide the means to download the documents. A P2P system should be equipped with capability of discovering the locations of peers but the current version of PBDMS does not have that capability. It requires users to know the IP addresses of their peers and any changes in a user’s IP address would require the user to inform his or her peers of the new IP. Current version of PBDMS does not support instant messaging and file transferring which are popular in most of the P2P systems. It also does not provide users with a capability to track the newest items in a peer’s library. To address these issues, the author has implemented a new version of PBDMS. The new version of PBDMS is equipped with peer discovery protocol and authentication protocol. It is also equipped with the capability to manage friends’ public key and classify friends as trusted or untrusted friends. A visual view that shows the status of friends (online and offline) and cryptography functionalities such as generation of new key-pair, encryption, decryption and etc are implemented. New functionalities such as instant messaging, file transferring, RSS-like subscription and web-of-trust operations are also implemented as well. As instant messaging and file transferring only works for online friends, it is important to extend these functionalities to offline friends. The new version of PBDMS is implemented with an offline mailbox infrastructure that can deliver messages and files to offline friends